Functional food in athletes - Deibert, P.; Ewald, A.; Berg, A. (2002)
Beneath a beneficial effect, physical exercise means stress to the organism. To an exhaustion of antioxidative capacity with the possible consequences of cell damage, lipid oxidation, or inflammatory responses, there is a suppressing effect of strenuous exercise on the immune system. A simple method to counteract all these side effects of physical activity without having adverse events itself is desirable. Probiotics (i.e., strains of Lactobacillus and Bifidobacterium) combine some of the features needed. Immune enhancement and reinforcement of host defense by modifying unspecific and humoral immunocompetence has been documented. A basic approach has been made to an alternative: modifying intestinal flora by feeding the favorable strains with prebiotics, as oligofructose or inulin. Prebiotics do even more than only promote bifidobacterial and lactobacillar growth, however, and several other intestinal bacteria are clearly involved in their metabolism. Yet the data from controlled studies in prevention of specific diseases are not validated in the same manner as for probiotics. In addition, phytochemicals have additional effects completing possibilities of pre- and probiotics. The antioxidant potential often exceeds that of comparable amounts of vitamins C and E. Diet should contain enough fresh fruits and vegetables to cover recommendations of daily intake, as the health-promoting effect has been well-documented in epidemiological studies. Until now, because the general health-promoting effect of pre- and probiotics among healthy, physically active people has not been clarified, these compounds may be indicated in select cases.